2015
DOI: 10.1080/19443994.2015.1096833
|View full text |Cite
|
Sign up to set email alerts
|

Modified synthesis of nanoscale zero-valent iron and its ultrasound-assisted reactivity study on a reactive dye and textile industry effluents

Abstract: A B S T R A C TSynthesized nanoscale zero-valent iron (NZVI) particles were applied for the degradation of a reactive dye Remazol Black B 133 and textile effluent. XRD and HR-TEM analysis of the synthesized particles showed body centered cubic crystal packing. The aggregates were spherical in shape and the size of the particles ranged from 5 to 15 nm. The reactive dye solution was substantially degraded by NZVI particles using ultrasonic irradiation under various experimental conditions created by varying NZVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 39 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…Usage of cysteamine hydrochloride renders the whole synthesis process less hazardous than conventional chemical methods. Furthermore, we have studied the photocatalytic efficiency of both hollow spheres of ZnS and RGO-ZnS composite in the presence of a model “azo” dye (Direct Blue 53) and then it was applied on a real textile effluent to check the actual applicability of these photocatalyst. The most toxic chemical present in a textile effluent is the dye stuff itself, as more than 50% of dye mass gets dispersed to water during manufacturing and processing. RGO-ZnS composite is found to be more effective than ZnS hollow spheres in removal of textile effluent, and with the help of physicochemical and photoluminescence study, we attribute this observation to efficient electron–hole separation at the interface of the two semiconducting systems. However, it is important to mention here that both of our as-synthesized materials (ZnS hollow spheres and RGO-ZnS composite) act as potential photocatalysts even at very low doses (Tables S1 and S2) as compared to earlier reports. , , In summary, we have successfully synthesized well-dispersed, uniform hollow spheres of ZnS and RGO-ZnS nanocomposites using a novel, ecofriendly sulfur source and effectively explored them for the degradation of textile effluent.…”
Section: Introductionmentioning
confidence: 87%
“…Usage of cysteamine hydrochloride renders the whole synthesis process less hazardous than conventional chemical methods. Furthermore, we have studied the photocatalytic efficiency of both hollow spheres of ZnS and RGO-ZnS composite in the presence of a model “azo” dye (Direct Blue 53) and then it was applied on a real textile effluent to check the actual applicability of these photocatalyst. The most toxic chemical present in a textile effluent is the dye stuff itself, as more than 50% of dye mass gets dispersed to water during manufacturing and processing. RGO-ZnS composite is found to be more effective than ZnS hollow spheres in removal of textile effluent, and with the help of physicochemical and photoluminescence study, we attribute this observation to efficient electron–hole separation at the interface of the two semiconducting systems. However, it is important to mention here that both of our as-synthesized materials (ZnS hollow spheres and RGO-ZnS composite) act as potential photocatalysts even at very low doses (Tables S1 and S2) as compared to earlier reports. , , In summary, we have successfully synthesized well-dispersed, uniform hollow spheres of ZnS and RGO-ZnS nanocomposites using a novel, ecofriendly sulfur source and effectively explored them for the degradation of textile effluent.…”
Section: Introductionmentioning
confidence: 87%
“…The average crystallite size of the synthesized nZVI was determined using XRD via the Scherrer equation [ 23 ] as follows: where D is the size of particle in nm, θ is the Bragg angle obtained from 2 θ and corresponds to the peak intensity at the maximum, and β is the full width at half maximum (FWHM), [ 24 , 25 ]. The mean value of the calculated crystal size is found to be 10.23 nm.…”
Section: Resultsmentioning
confidence: 99%
“…They also noticed that one gram of nZVI removed approximately 749 mg of dye, by breaking the azo group into an amino group. They also suggested that dye removal efficiency was increased via increasing nanoparticles dosage [31]. Luo and coworkers demonstrated a complete removal of orange II dye using rectorite (a natural clay), as support for nZVI in 10 min treatment, while only 35% dye removal was observed by using unsupported nZVI [32].…”
Section: Introductionmentioning
confidence: 99%